RISE OF THE ORIENT IN ENGLISH ROMANTIC LITERATURE - Anuradha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the stories rooted in authentic Eastern themes in early English Romantic literature, focusing on their role in creating an extraordinary Eastern world and associated motifs. By analyzing these historically significant works, we clarify how the concept of Orientalism emerged in English literature. The article is grounded in the historical context of the formation of Eastern stories and highlights features such as the genuine Oriental settings and the ancient Oriental works that captivated foreign scholars and diplomats in the late eighteenth century. Oriental literature during this time reflected a broader shift in taste from neoclassicism to romanticism. In the first half of the century, writers of Oriental fiction and poetry often used Eastern material to moralize or satirize the shortcomings of their own culture.